2004
DOI: 10.1210/jc.2003-031601
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Disease and Cardiovascular Morbidity in Hypopituitary Adults with or without Growth Hormone Replacement Therapy

Abstract: A retrospective comparison was performed between 1411 hypopituitary adults without GH replacement [mean age, 56.9 (sd 18.6) yr] and the normal population in terms of fatal and nonfatal morbidity. A similar prospective comparison was then made in 289 hypopituitary patients on long-term GH replacement [mean age, 47.6 (sd 14.8) yr; mean duration of GH treatment, 60 months]. In the 1411 hypopituitary patients without GH replacement, overall mortality (P < 0.001), and the rates of myocardial infarctions (P < 0.01),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
6
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(217 citation statements)
references
References 38 publications
11
186
6
14
Order By: Relevance
“…In contrast to these previous studies, no increased SMR for deaths from cardiovascular diseases or malignancies were observed. The elevated SMR noted in the studied cohort and the excess mortality seen in female patients confirm the results of earlier studies (1,2,3,4,6,8). That said, the present study revealed a lower SMR in the KIMS study cohort as a whole compared with mortality studies reported in the literature, and an SMR close to 1 in males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to these previous studies, no increased SMR for deaths from cardiovascular diseases or malignancies were observed. The elevated SMR noted in the studied cohort and the excess mortality seen in female patients confirm the results of earlier studies (1,2,3,4,6,8). That said, the present study revealed a lower SMR in the KIMS study cohort as a whole compared with mortality studies reported in the literature, and an SMR close to 1 in males.…”
Section: Discussionsupporting
confidence: 91%
“…It is well-established that mortality is increased in patients with hypopituitarism (1,2,3,4,5,6,7,8,9). Recently, an extensive review was devoted to this subject (10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it remains to be established whether quantitative and qualitative changes of lipids are the main cause for the increased cardiovascular mortality and morbidity found in hypopituitary patients with GHD (39,40). Similarly, the lack of effect of GHRT on LDL size in the present study does not support the concept that a possible effect of GHRT on cardiovascular mortality, as recently suggested (41), is related to the effect of GH on lipid metabolism.…”
Section: Ghd Versus Controls (Pz)contrasting
confidence: 87%
“…Abnormally low GH was also deleteriously associated with higher fasting insulin, lower IGF-1, and higher HOMA index. Large waist circumference is a strong independent risk factor for insulin resistance, 38,39 and untreated GH deficiency is associated with an array of unfavorable cardiovascular risk factors and outcomes 23,24,[40][41][42][43] and may also be a risk factor for insulin resistance. 13,23,44,45 The risk profile for diabetes that we observed in ALL survivors with GH deficiency is notable.…”
Section: Discussionmentioning
confidence: 99%